Reclamation performance of vermicompost and trichocompost on chemical and microbiological properties of acidic and alkaline soil - Akter, A; Hossain, S (Journal of Biodiversity Conservation and Bioresource Management, 2025)
Use of biofertilizer to increase soil fertility for crop production is a general practice now but to reclaim soil acidity and alkalinity with it is somehow lesser known. This pot experiment was set up considering that idea for okra growth following completely randomized design (CRD) with three treatments (control, vermicompost, trichocompost) and three replications using acid soil (pH 4.77) and alkaline soil (pH 7.87). The results showed partial (pH 5.9) and complete (pH 6.4) neutralization of soil acidity by trichocompost and vermicompost whereas pH increased in alkaline soil but EC decreased significantly by both treatments. Besides, total OC, total N, total P, total K, total S all increased significantly (P < 0.05) in both soil (except S in alkaline soil) by both biofertilizer application but total Ca, Mg, Fe, Mn decreased in acid soil while results were mixed in alkaline soil. Application of both biofertilizer in both soils improved the abundance of soil quality indicator microbes (TABC, TCC, TFC), soil beneficial bacteria (PSB, PSF) and plant pathogen inhibitor significantly (P < 0.05). J. biodivers. conserv. bioresour. manag. 10(2), 2024: 99-106